(untitled) (American Journal of Business Management, Economics and Banking, 2025)
This article presents a comprehensive and detailed analysis of the impact of tax policy changes on state budget revenues. The study investigates recent tax reforms, adjustments in tax rates, improvements in incentive systems, and the digitalization of tax administration, and examines how these measures have influenced the formation, growth dynamics, and stability of budget revenues. The research highlights the role of tax policy in promoting economic growth, ensuring fiscal sustainability, and improving public financial management efficiency. It also addresses measures for reducing the shadow economy, expanding the tax base, and optimizing revenue collection. Based on analytical findings, practical recommendations are developed to enhance the effectiveness of fiscal policy, increase state budget revenues, and strengthen economic stability. The results provide both scientific and applied value, offering guidance for future improvements in national fiscal strategies and sustainable economic development.